Taxes to influence energy use in road transportation in Australia - Pearce, Prafula (2017)
The desire to achieve a shift towards renewable energy will be difficult to achieve without a change in the energy use in road transportation in Australia. The transport sector in Australia is heavily reliant on oil and is responsible for contributing 18.1%, of Australia's annual greenhouse gas emissions. This paper examines the current Australian tax policy and its inability to make an impact on transport choices that would reduce energy use and emissions and promote alternative energy use. Some of the current taxes such as the luxury car tax can be singled out as a tax that has passed its “use-by” date. The paper explores how the Australian Government can use targeted taxation measures in order to encourage the purchase of low energy consumption and low-emission vehicles, reduce the number of registered cars on Australian roads and control the use of cars as a means of personal transportation. A comprehensive tax measure suggested in this paper is the luxury energy tax based on the premise that energy use in transportation is a luxury and should be taxed appropriately in order to curb its use and bring about a behaviour change in the choice and usage of motor vehicles.